Historical and Cultural Aspects of Controlling - Kovaleva, Valentina Danilovna; Rusetskiy, Mikhail Gennad’evich; Okorokova, Olga Alekseevna; Frantsisko, Olga Yurievna; Antoshkina, Anna Vladimirovna (Journal of History Culture and Art Research, 2018)
The article reveals the essence of the notion "controlling" and investigates historical stages in the development of controlling. The characteristic features of each stage of evolution and their interrelation are presented and the effectiveness of controlling toolkit in improving the system of organizational-economic management is justified. The main provisions regarding controlling models are revealed and generalized; scientific schools of controlling and their differences are defined and major subsystems of controlling are presented. The main aspects reflecting the essence of the notion "culture" are studied; the role of culture in modern society and in the system of organizational-economic management is determined. Main definitions of the notion "culture", which are most appropriate for characterizing the subsystem of operational controlling, are analyzed. The key aspects of organizational culture characterizing operational controlling as a controlling subsystem are identified; internal and external factors that affect the formation of organizational culture and its changes are defined. Specific features of national culture and their influence on corporate culture of an economic entity are disclosed; characteristics of corporate culture that are taken into account in the process of preparing management decisions are reflected. The development prospects of organizational culture that are based on modern controlling conceptions are considered contributing to further improvement of economic entity’s organizational-economic management and to increasing effectiveness in management decisions.